TINDAK PIDANA PEREDARAN OBAT KERAS TANPA RESEP DOKTER - Meilisa Nurrohmah; Hufron Hufron (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Wherever the health industry is viewed as essential to human survival, it is the subject of heated debate. The term "health" refers to the dynamics of a healthy lifestyle, which can be viewed from various perspectives, including a fulfilling social life, a strong spiritual foundation, an understanding of the significance of health, the use of scientific disciplines to strike a work-life balance, and so on. Whenever the topic of health is brought up, it's hard to avoid referring to medicine. It is expressly stated in Health Law 36 of 2009 that persons involved in the distribution of drugs must be licensed. Of course, you know that there are many different categories of pharmaceuticals in the pharmaceutical industry; however, the distribution of hard drugs, also known as G-list drugs, requires special care. The current system for distributing hard narcotics is lax because in some locations, such medications can be acquired without the need for a prescription. Many people and organizations have been exposed as dealers and distributors of illicit substances. As a result, the author intends to elaborate on the nature of the laws governing the illegal distribution of hard drugs, the relative ease with which such substances can be purchased, the spectrum of abuse that can result from their use, and so on